2020
DOI: 10.3389/fnagi.2020.00263
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Working Memory Based on Mismatch Negativity Neurofeedback in Subjective Cognitive Decline Patients: A Preliminary Study

Abstract: Mismatch negativity (MMN) is suitable for studies of preattentive auditory discriminability and the auditory memory trace. Subjective cognitive decline (SCD) is an ideal target for early therapeutic intervention because SCD occurs at preclinical stages many years before the onset of Alzheimer’s disease (AD). According to a novel lifespan-based model of dementia risk, hearing loss is considered the greatest potentially modifiable risk factor of dementia among nine health and lifestyle factors, and hearing impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…This rewiring could be seen as a compensatory response employed by the brain in the face of SCD, wherein the brain attempts to preserve or reinstate functional connectivity by redistributing its resources to other regions. Identifying these hubs could hold significance in optimizing the effectiveness of therapeutic interventions, such as neurofeedback or transcranial stimulation, which target specific brain regions and their activity and have been used with success in SCD (86,87).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rewiring could be seen as a compensatory response employed by the brain in the face of SCD, wherein the brain attempts to preserve or reinstate functional connectivity by redistributing its resources to other regions. Identifying these hubs could hold significance in optimizing the effectiveness of therapeutic interventions, such as neurofeedback or transcranial stimulation, which target specific brain regions and their activity and have been used with success in SCD (86,87).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that SCD is linked to an elevated risk of developing Alzheimer's disease (AD) and progressive cognitive impairment, as evidenced by various clinical and neuroimaging studies (8,12). To investigate the key brain regions involved in SCD, biochemical, structural, and functional approaches have been utilized, with several regions such as the medial temporal and occipitoparietal regions being implicated (for review, see Wang et al, 2020). Graph theory is a useful methodology for investigating the human connectome.…”
Section: Introductionmentioning
confidence: 99%
“…These studies mainly investigate the decoding method of single-trial responses ( Brandmeyer et al, 2013 ) as well as the neural mechanism underling reward stimuli ( Moser et al, 2014 ; Zioga et al, 2019 ; Wang et al, 2021 ). Research in the literature demonstrates broad applications of ERP-based NF training in cognitive deficits, including Attention-deficit/hyperactivity disorder (ADHD), Post-traumatic stress disorder (PTSD), and Subjective cognitive decline (SCD) ( Askovic et al, 2020 ; Pei et al, 2020 ; Deiber et al, 2021 ). The main challenge of developing NF training using ERP is designing reward functions associated with components of ERP as the adjustment target in single-trial responses.…”
Section: Neurofeedback Training Beyond Electroencephalography Frequen...mentioning
confidence: 99%
“…For example, degree centrality (DC) shows many connections between cognition and behavior. The complex functional network of the brain is affected by brain diseases such as schizophrenia, Alzheimer's disease and PD (Xie et al, 2019;Li et al, 2020;Pei et al, 2020). Graph theory is a great way to uncover the impact of these diseases on brain function.…”
Section: Introductionmentioning
confidence: 99%